2017
DOI: 10.18632/oncotarget.16223
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-27 polymorphisms are associated with premature coronary artery disease and metabolic parameters in the Mexican population: the genetics of atherosclerotic disease (GEA) Mexican study

Abstract: Several studies suggest an important role of Interleukin-27 in the development of atherosclerosis. The aim of this study was to establish whether the IL-27p28 gene polymorphisms are associated with premature coronary artery disease and/or other cardiovascular risk factors. Four IL-27p28 gene polymorphisms were selected and genotyped in 1162 premature coronary artery disease cases and 1107 controls. rs26528 T and rs40837 A alleles were significantly associated with a lower risk of premature coronary artery dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 42 publications
(48 reference statements)
3
30
0
2
Order By: Relevance
“…In a large number of CAD cases belonging to the GeneID Chinese Han population, four IL-27p28 tag polymorphisms (rs181206, rs17855750, rs37833, and rs153109) were detected and after adjusting for confounding variables, the polymorphisms were not associated with CAD, age at disease onset or severity 137 . These results concur well with the findings of the Genetics of Atherosclerotic Disease (GEA) Study in a Mexican population, in which the rs181206 and rs17855750 IL-27p28 gene variants were not significantly associated with premature CAD 98 . However, Posadas-Sánchez et al reported a significant association (after adjusting for age, gender, body mass index, smoking habit, total abdominal fat, homeostatic model assessment-insulin resistance, aspartate aminotransferase, adiponectin, and uric acid) of both the rs26528 T and rs40837 A alleles with a decreased risk of developing premature CAD 98 .…”
Section: Il-27p28 Genesupporting
confidence: 89%
See 2 more Smart Citations
“…In a large number of CAD cases belonging to the GeneID Chinese Han population, four IL-27p28 tag polymorphisms (rs181206, rs17855750, rs37833, and rs153109) were detected and after adjusting for confounding variables, the polymorphisms were not associated with CAD, age at disease onset or severity 137 . These results concur well with the findings of the Genetics of Atherosclerotic Disease (GEA) Study in a Mexican population, in which the rs181206 and rs17855750 IL-27p28 gene variants were not significantly associated with premature CAD 98 . However, Posadas-Sánchez et al reported a significant association (after adjusting for age, gender, body mass index, smoking habit, total abdominal fat, homeostatic model assessment-insulin resistance, aspartate aminotransferase, adiponectin, and uric acid) of both the rs26528 T and rs40837 A alleles with a decreased risk of developing premature CAD 98 .…”
Section: Il-27p28 Genesupporting
confidence: 89%
“…These results concur well with the findings of the Genetics of Atherosclerotic Disease (GEA) Study in a Mexican population, in which the rs181206 and rs17855750 IL-27p28 gene variants were not significantly associated with premature CAD 98 . However, Posadas-Sánchez et al reported a significant association (after adjusting for age, gender, body mass index, smoking habit, total abdominal fat, homeostatic model assessment-insulin resistance, aspartate aminotransferase, adiponectin, and uric acid) of both the rs26528 T and rs40837 A alleles with a decreased risk of developing premature CAD 98 . In addition, luciferase assays showed that cotransfection of the rs40837 A allele and miR-379-5p significantly decreased luciferase gene expression.…”
Section: Il-27p28 Genesupporting
confidence: 89%
See 1 more Smart Citation
“…An IL-23R polymorphism was observed to be related to coronary artery disease, and the IL-23R rs6682925T/C polymorphism may independently relate to the presence of coronary artery disease (Zhang et al, 2014a). IL-27 gene polymorphism had no effect on the presence of subclinical atherosclerosis, while closely related to atherosclerosis and coronary artery disease, rs26528 T and rs40837 A alleles significantly reduced the risk of coronary artery disease (Posadas-Sánchez et al, 2017;Vargas-Alarcón et al, 2019). No research about gene polymorphisms of IL-12 and IL-35 and the presence of coronary artery disease was reported yet.…”
Section: Clinical Datamentioning
confidence: 96%
“…Equally, genetic variants associated with IL6st (gp130; rs10940495) and IL6R (rs2228145) are common to patients with cardiovascular disease and rheumatoid arthritis . Several polymorphisms linked with IL27 (encoding IL‐27p28; rs153109, rs181206, rs17855750) also display risk susceptibilities with asthma, certain cancers, metabolic disorders and some viral infections . For example, rs153109 is linked to more severe forms of rheumatoid arthritis .…”
Section: The Significance Of Genetic Polymorphisms Linked With Il‐6 Amentioning
confidence: 99%